Rocky Mountain National Park, Colorado 2001-2005 vegetation classification and mapping - Salas, David, author; Stevens, Joe, author; Schulz, Keith, author; United States. Bureau of Reclamation. Denver Office. Technical Service Center, publisher (Colorado State University. Libraries, 2005)
Rocky Mountain National Park (ROMO) encompasses 417 square miles in north central Colorado, and lies on the eastern slope of the southern Rocky Mountains. This mapping effort is part of the National Park Services' national inventory and monitoring program and will provide core or "baseline" information that park managers need to effectively manage and protect park resources. This vegetation inventory was conducted in accordance with specified protocols and quality assurance standards.
Not digitized by CSUL Digital Services.
On title page: Final report
Keywords: ecology; vegetation mapping and classification